Per- and polyfluoroalkyl substances in coastal plain water network areas: shifting management focus to sediments - Miao-Miao Wang; Zhiqiang Xia; Jianming Jiang; Haigang Wu; Hurong Huang; Xilong Zhang; Wen-Jun Hong; Minjie Li; Liang-Hong Guo (Frontiers in Marine Science, 2025)
Introduction Per- and poly-fluoroalkyl substances (PFAS) are of great concern due to harm to human and wildlife health. Local-scale studies, especially those focused on ecologically important or densely populated areas, are critical to effective management, such as prioritizing resource allocation. Methods To prioritize management efforts, we investigated the distribution of PFAS in a densely populated coastal plain water network area in east China, followed by health and ecological risk assessments. Results Results demonstrated that ∑18PFAS (212.86-406.73 ng/L) in water had non-significant seasonal and weak spatial variations. Individual congeners, not the ∑PFAS concentrations, were significantly correlated with some water quality parameters. ∑PFAS in sediments, not surface water, demonstrated a significant negative relationship with river width. The perfluoroalkyl carboxylic acids (PFCAs) dominated the PFAS (water: 84.9%; sediments: 76.9%), while sediments harbored more perfluoroalkyl sulfonic acids than surface water (PFSAs; 23.1% vs. 15.1%). Spatial variation of ∑PFAS was much more profound in sediments than surface water (CV: 83.7% vs. 14.1-46.3%). Despite a low-moderate risk to water birds (RQ: 0.069-0.16), we found neither evident ecological risks to other aquatic organisms (RQ < 0.01) nor human health risks of the water PFAS. Discussion Our findings revealed the divergent distribution pattern of PFAS in surface water versus sediments in coastal plain water network areas, likely due to presumable well-mixed conditions caused by tidal cycles and local water level regulations. Our work suggests that management focus of PFAS pollution should be shifted to sediments to optimize resource allocation in such coastal plain water network areas.